Metaplastic breast cancer with chondroid differentiation - Zin W. Myint; Sandeep Raparla; Lois K. Kamugisha (Greater Baltimore Medical Center, 2015)
Background: Metaplastic carcinoma of the breast is an extremely rare subtype of breast cancer with an incidence of <1% of all breast neoplasms. Metaplastic carcinoma with chondroid differentiation is the rarest among all histologic subtypes of breast cancer. We report a case of infiltrating ductal carcinoma with metaplastic features of chondroid differentiation. Case presentation: A 58-year-old-woman presented to our clinic with a 4-month history of a lump in her right breast. On examination, a firm non-tender mass measuring 2×2 cm was noted in the right upper outer quadrant. It was not attached to the underlying structures. Mammography revealed a dense irregular mass in the axillary tail and a circumscribed nodule in the 6 O'clock periareolar region. This was a new development compared to the patient's most recent screening mammogram performed 2 years and 6 months previously. Ultrasound demonstrated a lobulated solid mass in the axillary tail and a simple cyst in the 6 O'clock periareolar region. Biopsy of the areolar region of the right breast revealed atypical duct hyperplasia. Fine needle aspiration cytology of the right breast axillary tail revealed a poorly differentiated invasive carcinoma consistent with mammary duct origin. On histopathological examination, it was an infiltrating ductal carcinoma with metaplastic features of chondroid differentiation. The tumor was estrogen receptor, progesterone receptor, and HER-2 negative with 0% nuclear staining. Ki-67 index was 52% with strong nuclear staining. The overall ELSTON grade of invasive carcinoma was grade 3. The patient received adjuvant chemotherapy with AC-T (adriamycin, cytoxan, and taxol) and is currently undergoing surveillance for recurrent disease. Conclusion: Metaplastic breast cancer is an extremely rare subtype of breast carcinoma. Initial management of localized disease consists of wide excision with clear surgical margins followed by radiation or mastectomy and sentinel lymph node biopsy. Although standard breast chemotherapy regimens such as AC-T are routinely used in metaplastic breast cancer in both adjuvant and metastatic settings, outcomes are significantly inferior to other breast subtypes. Further studies are required to explore targeted treatment to achieve better outcomes in this patient population.